Sistem Keuangan Tanpa Riba Dalam Pemikiran Ekonomi Islam Kontemporer Solusi Atas Krisis Utang Dan Ketimpangan Pembiayaan Di Indonesia - Alya Nur Fadiyah Fahdatun Nabilah; Arian Farid As Sidik; Gebi Firyanti Nurusman; Sri Wigati (Jurnal Manajemen Perbankan Keuangan Nitro, 2026)
This study aims to analyze the concept of a riba-free financial system in contemporary Islamic economic thought and its relevance as a solution to Indonesia’s debt crisis and financing inequality. The research employs a qualitative-descriptive library method by examining the works of modern Islamic economic scholars and data related to national financing conditions. The findings show that a riba-free financial system, based on the principles of justice, profit-and-loss sharing, and transparency, offers a more stable and inclusive alternative compared to interest-based mechanisms. The application of these principles has the potential to reduce household debt burdens, expand financing access for MSMEs, and improve economic distribution. Therefore, the Islamic financial system provides a significant contribution to strengthening Indonesia’s financing structure. Keywords: Islamic Economics, Financing Inequality, Debt Crisis, Riba, Financial System